2012
DOI: 10.1093/hmg/dds090
|View full text |Cite
|
Sign up to set email alerts
|

Disruption and therapeutic rescue of autophagy in a human neuronal model of Niemann Pick type C1

Abstract: An unresolved issue about many neurodegenerative diseases is why neurons are particularly sensitive to defects in ubiquitous cellular processes. One example is Niemann Pick type C1, caused by defects in cholesterol trafficking in all cells, but where neurons are preferentially damaged. Understanding this selective failure is limited by the difficulty in obtaining live human neurons from affected patients. To solve this problem, we generated neurons with decreased function of NPC1 from human embryonic stem cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
96
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(111 citation statements)
references
References 50 publications
12
96
2
Order By: Relevance
“…In contrast to this notion, however, autophagy activation in NP-C was recently shown to impair both mitochondrial turnover 26 and lysosomal protease function. 27 Using human embryonic stem cell-derived neurons, it was shown that both induction of basal autophagy and impaired autophagic flux concomitantly occur with NPC1 knockdown and that this significantly compromises mitochondrial clearance.…”
Section: Reviewmentioning
confidence: 86%
See 2 more Smart Citations
“…In contrast to this notion, however, autophagy activation in NP-C was recently shown to impair both mitochondrial turnover 26 and lysosomal protease function. 27 Using human embryonic stem cell-derived neurons, it was shown that both induction of basal autophagy and impaired autophagic flux concomitantly occur with NPC1 knockdown and that this significantly compromises mitochondrial clearance.…”
Section: Reviewmentioning
confidence: 86%
“…27 Using human embryonic stem cell-derived neurons, it was shown that both induction of basal autophagy and impaired autophagic flux concomitantly occur with NPC1 knockdown and that this significantly compromises mitochondrial clearance. 26 Remarkably, these changes were partially reversible through the application of the autophagy inhibitor 3-methyladenine, which reduces autophagosome formation and, by treatment with cyclodextrin, a compound capable of mobilizing cholesterol from the lysosomal compartment. 26 Concurrent with the notion that NPC deficiency interferes with the completion of the autophagic cascade, recent findings demonstrate that the autophagic response increases delivery of cholesterol to the lysosome and thereby causes dysfunction of lysosomal proteases, which in turn could impair turnover of autolysosomes, therefore creating a pathological feedback loop that promotes induction of dysfunctional autophagy 27 (Figure 3).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the cholesterol content of mitochondria isolated from brains is increased, not decreased, by NPC1 deficiency ( 40,41 ). Several properties of mitochondria such as ATP production, oxidative stress, and possibly mitophagy are altered by NPC1 defi ciency (41)(42)(43), probably because of the increase in mitochondrial cholesterol. In contrast to defi ciency of NPC1, however, the movement of endosomal cholesterol to mitochondria is disrupted by NPC2 defi ciency ( 44 ).…”
mentioning
confidence: 99%
“…In addition, a basal autophagy plays a pivotal role in the constitutive turnover of cytoplasmic components for maintaining cellular function. [26][27][28][29] Indeed, the impairment of basal autophagy has been reported in various neurodegenerative diseases and lysosomal storage disorders including NPC. 30,31) Therefore, an amelioration of impaired autophagy is still a challenging issue for the treatment of NPC.…”
Section: Cytotoxicity Of R8-β-cydmentioning
confidence: 99%